The synthesis of a multiple D-A conjugated macrocycle and its application in organic photovoltaic - Liu,W; Zhang,H; Liang,S; Wang,T; He,S; Hu,Y; Zhang,R; Ning,H; Ren,J; Bakulin,A; Gao,F; Yuan,J; et al. (Angewandte Chemie International Edition, 2023)
As a novel class of materials, D–A conjugated macrocycles hold significant promise for chemical science. However, their potential in photovoltaic remains largely untapped due to the complexity of introducing multiple donor and acceptor moieties into the design and synthesis of cyclic π-conjugated molecules. Here, we report a multiple D–A ring-like conjugated molecule (RCM) via the coupling of dimer molecule DBTP-C3 as a template and thiophenes in high yields. RCM exhibits a narrow optical gap (1.33eV) and excellent thermal stability, and shows a remarkable photoluminescence yield (ΦPL) of 11.1 % in solution, much higher than non-cyclic analogues. Organic solar cell (OSC) constructed with RCM as electron acceptor shows efficient charge separation at donor-acceptor band offsets and achieves a power conversion efficiency (PCE) of 14.2 %-approximately fourfold higher than macrocycle-based OSCs reported so far. This is partly due to low non-radiative voltage loss down to 0.20eV and a high electroluminescence yield (ΦEL) of 4×10−4. Our findings emphasize the potential of D–A cyclic conjugated molecules in advancing organic photovoltaic technology.